When More Blame is Better than Less: The Effects of Internal and External Attributions for Repairing Trust after a Competence- or Integrity-Based Trust Violation - KIM, Peter H. (Institutional Knowledge at Singapore Management University, 2006)
This study examines the trust repair implications of apologizing with an internal vs. external attribution after a competence- vs. integrity-based trust violation. By considering theory regarding differences in the perceived diagnosticity of information about competence vs. integrity, we note that the conditions where external attributions would be more necessary for mitigating oneÆs blame are precisely the conditions where such external attributions are less likely to be believed. Moreover, empirical studies that have compared the relative benefits of external and internal attributions for repairing trust have reached conflicting conclusions regarding the response that should be used. We asked 189 college students to respond to videotaped scenarios in which they were asked to play the role of a manager and make decisions about hiring an accountant who had misfiled a tax return with a prior employer. Each participant was presented with one of four scenarios, which differed with respect to the type of violation (competence vs. integrity) and type of response (apology-internal vs. apology-external). The results revealed a significant interaction whereby trust was repaired more successfully when mistrusted parties apologized with an internal, rather than external, attribution when the trust violation concerned matters of competence, but apologized with an external, rather than internal, attribution when the trust violation concerned matters of integrity. These findings suggest that being guilty of an integrity-based violation can be so detrimental for trust that any mitigating response, even one that perceivers are likely to question, may prove worthwhile.